Framework of the culture of innovation : a revisit - Wan Ismail, Wan Khairuzzaman; Abd. Majid, R. (Faculty of Management and Human Resource Development, 2007)

(untitled)
Innovation is a complex and multifaceted phenomenon and is influenced by many factors. It may be an environment or a culture - almost spiritual force - that exists in a company which drives value creation. From an organizational point of view, culture has multiple elements which can serve to supplement an organization's capability towards innovation. Thus, inculcating a culture of innovation is seen as a vital requirement to provide organizations with necessary ingredients to innovate. Different approaches have been implemented with the aim of capturing a framework thriving under enabling conditions and in an atmosphere of receptivity. However, most of the work thus far focuses only on particular elements of culture of innovation. This conceptual paper draws upon a wide range of theoretical and empirical models to deduce a holistic framework. The resulted framework includes human factors and cultural-based determinants which are always dynamic and contextual. Ultimately, the paper emphasizes the importance of a broad framework which covers the interconnected dimensions in generating a culture of innovation